IMPLEMENTASI NILAI KETUHANAN DALAM P5 (PROJEK PENGUATAN PROFIL PELAJAR PANCASILA) BAGI ANAK MI IMPLEMENTATION OF DIVINE VALUES ​​IN P5 (STRENGTHENING PANCASILA STUDENT PROFILE PROJECT) FOR MI CHILDREN - Auliya Syafa’atul Udzmah; Nailis Syarifah; Fu’ad Arif Noor (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
This research aims to determine efforts to increase students' divine values ​​by implementing divine values. The application of divine values is an awareness and is designed to prepare students in terms of knowledge and understanding, life and practice, and to help them believe in the religion that is part of them. This research uses the literature study method. The literature study method is a series of activities relating to methods of collecting library data, reading and taking notes, and managing research materials. . This writing uses an approach by utilizing facts and supporting sources, such as ebooks, articles and a number of related journals. The results of the research show that implementing divine values ​​can increase the tolerant character of students at school. It is very important to do this, because implementing divine values ​​can build character in students.Keywords: implementation, divinity, p5